Hot-formed steel laser splicing welding joint and manufacturing method and application thereof

By adjusting the proportion of weld elements and the quenching heat treatment and cooling process during the welding process of thermoformed steel, the base material and welds of the welded joints are tempered martensite, which solves the problem of insufficient performance of the welded joints and achieves high efficiency , low-cost welded joint production.

CN119457422APending Publication Date: 2025-02-18SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411478320.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the welded joint performance of thermoformed steels, especially in terms of tensile strength, elongation and anti-hydrobrittle sensitivity, and there is a problem of residual stress and strong plasticity mismatch after welding.

Method used

By simultaneously transporting certain components of welding wires during the welding process, the proportion of weld elements is controlled, and by controlling the quenching heat treatment and cooling process, the base material and welds are both tempered and martensite, thereby realizing the base material and welds. strong plasticity matching.

Benefits of technology

The tensile strength, elongation and anti-hydrobrittle sensitivity of welded joints are significantly improved, manufacturing cost and production time are reduced, and the welding method is suitable for applications in different environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119457422A_ABST
    Figure CN119457422A_ABST
Patent Text Reader

Abstract

The invention discloses a laser splicing welding joint for ultrahigh-strength hot-formed steel and a manufacturing method of the laser splicing welding joint, the welding joint comprises a base metal area and a melting area, and the base metal area and a welding line area are mainly composed of tempered martensite; the mass percent of the carbon content in the base metal area is not lower than 0.2%, and the mass percent of the average aluminum content in the weld joint area is not higher than 1.8%. The welding joint is manufactured through the following steps that a pair of high-strength steel workpieces is provided to be in butt joint to execute laser welding, and in the welding process, laser filler wire welding is adopted to obtain a preliminary welding seam; performing a quenching process on the primary welding seam to obtain a final welding seam; the quenching process comprises a heating and heat preservation stage and a cooling stage; the time for quickly transferring and cooling the welding part is t1, and the temperature of the welding part is T1; the cooling stage comprises a stage from T1 to the temperature T2 and a stage from T2 to the room temperature through slow cooling, the duration time of the rapid cooling stage is t2, and the duration time of the stage from slow cooling to the room temperature is t3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the manufacture of high-strength steel coated plate welding parts, and in particular to a hot-formed steel laser welding joint and a manufacturing method and application thereof. Background Art

[0002] In some fields, especially in the manufacture of automobile and aerospace parts, the use of materials requires high corrosion resistance, so more and more materials with coatings on the surface are used. Since the steel with aluminum or aluminum alloy coated on the surface manufactured by cold rolling or hot rolling not only has good corrosion resistance, but also has high high temperature resistance, which is conducive to the manufacture of certain parts by hot processing, the steel plate with aluminum alloy coated on the surface is especially used in the manufacture of automobile bodies, and is used in automobile structural parts, such as door reinforcements, B-pillar structural parts, roof reinforcements and other parts, especially in the application of ultra-high strength hot stamping plates, so as to achieve high corrosion resistance, reduce the weight of the automobile body, and improve collision absorption energy.

[0003] At the same time, in the automotive manufacturing industry, in order to reduce vehicle weight and achieve lightweight goals, more and more materials of equal thickness, unequal thickness, homogeneous and heterogeneous qualities are first welded, and then the welded parts are hot stamped to achieve better weight reduction and cost reduction. The laser welding method is the preferred method of this approach, with higher quality, higher efficiency and better flexibility, and is called "laser welded plates". High-strength martensitic steel structural parts are often obtained by first laser butt welding the flat workpiece and then hot stamping and quenching the workpiece with the weld. During hot stamping, the weld structure is first heated to a temperature exceeding the AC3 temperature of the steel workpiece for complete austenitization, and then cooled at a speed exceeding the critical cooling rate of the martensitic phase transformation to obtain the final welded parts.

[0004] At present, the strength level of hot-formed steel is getting higher and higher. For ultra-high strength hot-formed parts with tensile strength exceeding 1500Mpa after quenching, due to the low martensitic phase transformation point, the quenching cooling speed is fast and the degree of self-tempering is insufficient, the structure is all hardened quenched martensite, the parent material and weld area have large residual stress, and the risk of hydrogen embrittlement is also high, which reduces the strength and plasticity of the material. At the same time, for hot-formed steel with tensile strength exceeding 1500Mpa, the joint performance is reduced. The element difference between the parent material area and the weld area will lead to a mismatch between strength and plasticity, and high cracking sensitivity. How to make the hot-formed steel welded joint after quenching have higher joint performance is a major problem.

[0005] Patent publication number CN108356417B (hereinafter referred to as Patent Document 1) provides a heat treatment method for improving the plasticity of laser welded joints of high-strength and medium-plastic manganese steel. The welded joints are heat treated at a temperature of 650 to 750°C, and the martensite in the weld zone is transformed into austenite and ferrite. However, this method is not suitable for welding applications of hot-formed steel.

[0006] The patent with publication number CN112222667B (hereinafter referred to as Patent Document 2) provides a post-weld treatment method for improving the performance of medium manganese steel spot welding joints. However, this method is suitable for medium manganese steel (manganese content is 4%-12% by mass), and better tensile shear performance requires insulation at the two-phase temperature, which is not suitable for the application of hot-formed steel.

[0007] The patent with publication number CN118237457A sets the austenitizing temperature before hot forming lower than the complete austenitizing temperature AC3, so that the final quenched structure contains ferrite structure to reduce internal stress and improve hydrogen embrittlement sensitivity. However, the introduction of ferrite into the structure will undoubtedly reduce the tensile strength of the material.

[0008] The patent with publication number CN117737372A obtains hot-formed steel with a tensile strength exceeding 2150Mpa by adding Cu element to hot-formed steel and performing water-cooling quenching after failure. The long aging time and the addition of additional copper elements undoubtedly increase the manufacturing cost. At the same time, water cooling treatment will still result in large residual stress and deformation.

[0009] The patent with publication number CN118581377A controls the ferrite content before hot forming by controlling the cooling rate and temperature in the continuous annealing process of hot forming steel, and finally reduces the original austenite grain size after hot stamping and improves the mechanical properties of the material. However, it is not applicable to welded joints, as the microstructure distribution of welded joints has changed after welding and remelting.

[0010] The patent with publication number CN117070845A obtains hot-formed steel parts with high crack sensitivity by locally tempering the parts by gradient heating after quenching, and keeping the parts warm for 10-20 minutes. Although this method can obtain parts with better performance, the complex and time-consuming post-processing process will reduce manufacturing efficiency and increase manufacturing costs.

[0011] The patent with publication number CN116748681A reduces the hydrogen embrittlement sensitivity of hot-formed steel laser welding joints by simultaneously setting a preheating module and a slow cooling module during the laser welding process. The process is relatively complex and costly, and is only applicable to uncoated steel and has a small scope.

[0012] Therefore, a better method is needed to achieve high-efficiency and high-performance laser welding of hot-formed steel. Summary of the invention

[0013] In order to overcome the shortcomings of the above-mentioned prior art, the present invention provides a high-performance hot-formed steel laser welding joint and its manufacturing method and application. The welding joint controls the element ratio in the weld by synchronously delivering a welding wire with a certain composition during the welding process, and controls the subsequent quenching heat treatment cooling process to obtain a final base material and weld that are both martensite in a certain tempered state, so that the base material and the weld achieve a strength-plasticity match, thereby improving the comprehensive mechanical properties of the entire welding joint.

[0014] The solution of the present invention is as follows:

[0015] On the one hand, the present invention provides a hot-formed steel laser welding joint, which is characterized in that: the welding joint includes a base metal area and a weld melting area; wherein the average micro-Vickers hardness of the base metal area and the melting area is HV BM 、HV FZ , and meet HV BM / HV FZ Between 0.8-1.2, HV BM ≥470HV , The microstructures of the base metal area and the weld area are composed of tempered martensite, and the carbon content of the base metal area is not less than 0.2% by mass, and the average aluminum content of the weld area is not higher than 1.8% by mass.

[0016] Preferably, the HV BM / HV FZ Between 0.85-1.1.

[0017] Preferably, the average aluminum content in the weld zone is not higher than 1.5% by mass.

[0018] Preferably, HV BM ≥520HV, and the carbon content in the parent metal area is not less than 0.25% by mass.

[0019] Preferably, HV BM ≥550HV, and the carbon content in the parent metal area is not less than 0.30% by mass.

[0020] On the other hand, the present invention also provides a method for manufacturing a hot-formed steel laser welding joint, wherein the method comprises the following steps:

[0021] Providing a pair of high-strength steel workpieces butted together to form an assembly;

[0022] Performing laser welding on the assembly to form a preliminary weld joint, wherein an initial weld molten zone forms quenched martensite;

[0023] The preliminary welded joint is subjected to a quenching treatment, including a heating and insulation stage and a cooling stage:

[0024] Heating and holding stage: the weld joint is kept in an environment of temperature T0 for a holding time t0, wherein T0 is 820-980°C, t0 is 150-500s, t0≥B*150, B is the thickness of the assembly, in mm, so that the quenched martensite in the initial weld melting zone is transformed into austenite, and the base material zone forms austenite;

[0025] Cooling stage: divided into rapid cooling stage and slow cooling stage.

[0026] The rapid cooling stage refers to the rapid transfer and rapid cooling of the joint after heating and heat preservation, wherein the transfer time is t1, t1≤15s, the initial temperature of rapid cooling is T1, T1≥600°, and the cooling time from T1 to T2 is not less than 30° / s, so that the parent material area and the weld melting area are transformed into quenched martensite, wherein 2≤t2≤20s; 150℃≤T2≤Ms-50℃, Ms is the critical temperature of martensitic phase transformation of high-strength steel substrate;

[0027] Slow cooling stage: The base metal area and the weld melting area are cooled to room temperature, and self-tempering occurs to transform the quenched martensite into tempered martensite.

[0028] Preferably, at least one surface of the steel workpiece has an aluminum coating.

[0029] Preferably, T0>930-400C-15Mn+50Si+5Cr; wherein C, Mn, Si and Cr are the mass percentage contents of the elements contained in the high-strength steel substrate.

[0030] Preferably, the carbon content of the steel substrate is not less than 0.2% by mass.

[0031] Preferably, the carbon content of the steel substrate is not less than 0.25% by mass.

[0032] Preferably, a laser wire-filling welding method is adopted in the laser welding process, and austenitizing elements Ni, Mn and C are synchronously transported into the weld molten pool during the welding process.

[0033] Preferably, the martensitic transformation critical temperature Ms of the steel substrate does not exceed 400°C.

[0034] Preferably, the tensile strength of the steel substrate after final quenching is not less than 1500 MPa.

[0035] Thirdly, the present invention also provides the use of the components containing the above-mentioned welded joint or obtained by the above-mentioned method in structural components or safety components of mechanized land motor vehicles.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1) High efficiency and short time in the heat treatment process can reduce internal residual stress, significantly reduce manufacturing costs, improve production efficiency, and obtain high-performance welded joints. The obtained welded joints have high tensile strength and elongation, as well as high resistance to hydrogen embrittlement sensitivity, high corrosion resistance, and surface wear resistance. At the same time, the welding method can be used for various environments with different gaps and has high adaptability.

[0038] 2) By delivering welding wire with simple composition, the cost is low and the operation is simple. The hot-formed steel laser welding joint ensures the uniformity of the overall hardness of the welded joint by precisely controlling the average micro-Vickers hardness ratio of the base material area (HVBM) and the weld molten zone (HVFZ) (HVBM / HVFZ is between 0.8-1.2), avoiding stress concentration and brittle fracture problems caused by excessive hardness differences. When HVBM / HVFZ is between 0.85-1.1, the uniformity of the hardness distribution is further optimized, which improves the mechanical properties and durability of the joint.

[0039] 3) The microhardness of the parent material area HVBM ≥ 470HV, and the high strength characteristics of the parent material are guaranteed by adjusting the carbon content (not less than 0.2%). When HVBM ≥ 520HV or 550HV, the strength of the parent material is further improved to meet the application requirements of higher strength. The weld zone structure is composed of tempered martensite, and the average aluminum content in the weld zone is controlled to be no more than 1.8% by mass (preferably no more than 1.5%), which not only ensures the toughness of the weld, but also avoids the embrittlement of the joint caused by excessive aluminum content. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0041] Figure 1 Shown is a schematic flow chart of the method of the present invention.

[0042] Figure 2 Shown is a schematic cross-sectional view of a steel workpiece involved in the present invention.

[0043] Figure 3It is a schematic diagram of two workpieces butted together to form an assembly in the present invention.

[0044] Figure 4 Shown is a schematic diagram of the laser welding process implemented in the present invention.

[0045] Figure 5 Shown is a schematic top view of the laser welding process implemented in the present invention.

[0046] Figure 6 Shown is a schematic diagram of the cross section of the weld obtained in the present invention.

[0047] Figure 7 Shown is a schematic diagram of the timing of the quenching process used in the present invention.

[0048] Figure 8 Shown is another schematic diagram of the timing of the quenching process used in the present invention.

[0049] Fig. 9 Shown is a metallographic image of a weld cross section obtained in the present invention.

[0050] Fig.10 Shown Fig. 9 Internal organizational structure diagram of the weld in the embodiment.

[0051] Fig.11 Shown Fig. 9 The tensile curve, mechanical properties and fracture diagram of the welded joint obtained in the embodiment.

[0052] Fig.12 Shown is a metallographic image of a weld cross section obtained in the present invention.

[0053] Fig.13 Shown Fig.12 Internal organizational structure diagram of the weld in the embodiment.

[0054] Fig.14 Shown Fig.12 The tensile curve, mechanical properties and fracture diagram of the welded joint obtained in the embodiment.

[0055] Fig.15 Shown is a metallographic image of a weld cross section obtained in the present invention.

[0056] Fig.16 Shown Fig.15 Internal organizational structure diagram of the weld in the embodiment.

[0057] Fig.17 Shown Fig.15 The tensile curve, mechanical properties and fracture diagram of the welded joint obtained in the embodiment.

[0058] Fig.18Shown is a metallographic image of a weld cross section obtained in the present invention.

[0059] Fig.19 Shown Fig.18 Internal organizational structure diagram of the weld in the embodiment.

[0060] Fig. 20 Shown Fig.18 The tensile curve, mechanical properties and fracture diagram of the welded joint obtained in the embodiment.

[0061] Fig.21 Shown is a metallographic image of a weld cross section obtained in the present invention.

[0062] Fig. 22 Shown Fig.21 Internal organizational structure diagram of the weld in the embodiment.

[0063] Fig.23 Shown Fig.21 The tensile curve, mechanical properties and fracture diagram of the welded joint obtained in the embodiment.

[0064] Fig.24 The tensile fracture surface obtained in Comparative Example 1 is shown.

[0065] Fig.25 The tensile fracture surface obtained in Comparative Example 2 is shown.

[0066] Figure numerals, 11-first steel workpiece, 12-second steel workpiece; 111-upper surface coating of the first steel workpiece; 112-lower surface coating of the first steel workpiece; 12-second steel workpiece; B-butt gap; 3-laser beam; 4-welding wire; 5-molten pool; 6-weld; h10-residual height of upper surface of weld; h11-residual height of lower surface of weld; T0-heating and insulation temperature; t0-heating and insulation time; T1-temperature during rapid cooling; t1-transfer time of the joint from T0 to T1; t2-time for rapid cooling; T2-end time of rapid cooling; t3-time for slow cooling. DETAILED DESCRIPTION

[0067] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the present invention is further described below in conjunction with the embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, the accompanying drawings are schematic diagrams, so the device and equipment of the present invention are not limited by the size or ratio of the schematic diagrams.

[0068] It should be noted that in the claims and description of this patent, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "including one" do not exclude the existence of other identical elements in the process, method, article or device including the elements. The final weld in the present invention refers to the laser welded joint.

[0069] The present invention provides a method for manufacturing a high-strength laser welding joint. Figure 1 , which is divided into three steps as a whole, namely, first providing a pair of high-strength steels before hot forming for docking, then performing laser welding to obtain a preliminary welded joint, and finally performing quenching heat treatment on the preliminary welded joint. The high-strength steel mentioned in the present invention is a steel that can be transformed into hot-formed steel after hot stamping, which is well known in the art; the base material generally has ferrite and pearlite before forming, wherein the carbon content is not less than 0.1%, and has a boron content of about 0.002-0.006 to meet the hardenability of the subsequent quenching process, and can form a full martensitic structure after quenching, and has a higher strength. The tensile strength of a typical boron steel is not less than 500Mpa. The typical steel plate base material is grade 22MnB5, and the elements contained are mainly as follows: 0.15% ≤ C ≤ 0.45%; 0.5% ≤ Mn ≤ 2.5%; 0.08% ≤ Si ≤ 0.4%; Al ≤ 0.45%; 0.01% ≤ Cr ≤ 0.5%; Ti ≤ 0.1%; Nb ≤ 0.1%; V ≤ 0.1%; S ≤ 0.05%; P ≤ 0.05%; 0.002% ≤ B ≤ 0.006%; the rest are Fe and unavoidable impurities. As a material with a higher strength level, it is generally added with more alloy elements such as C, such as 34MnB5, 28MnB5, 37MnB4 and other typical grades, whose tensile strength can exceed 2000Mpa. As a representative of higher strength, the mass fraction of its carbon content is higher than 0.25%.

[0070] Steel workpieces generally have a coating on at least one side, such as Figure 2 The first steel plate 11 shown has a first surface coating 111 and a second surface coating 112. Generally, the coatings are composed of aluminum and silicon, wherein the aluminum content is not less than 80%, preferably more than 85%, wherein the total coating thickness b is generally 5-50 μm.

[0071] Figure 3 The figure shows a schematic diagram of workpiece assembly. The two workpieces 11 and 12 can be made of exactly the same materials, or can be made of materials with different thicknesses, coating types, or strengths. The thickness of the two workpieces is generally 0.8-3.0 mm. The two workpieces are butt-jointed to form an assembly, and the butt-joint gap is B, which is 0-0.5 mm. Figure 4 The laser welding process is shown in FIG. 1 , wherein a laser beam 3 and a welding wire 4 are provided to point to the joint position of the assembly, and then the laser beam is emitted and the wire is fed synchronously to melt the assembly and the welding wire to form a molten pool 5, and then a preliminary laser welding seam 6 is formed along the welding path. Figure 5 The figure shows a schematic diagram of a laser welding process from a top view. In this process, the laser beam is generally emitted by a laser, wherein the laser may include various types, such as a solid-state laser beam or a gas laser beam, specifically including a fiber laser, a disk laser, a semiconductor diode laser, and a Nd:YAG solid-state laser, or a CO2 gas laser. Of course, other types may also be included, as long as they can generate a laser beam and generate a keyhole and a molten weld pool. In the welding process, the laser beam may also be composed of one or more light spots, and the beam energy distribution may be in various forms such as Gaussian distribution, average distribution, or point ring distribution. In the welding process, the laser beam may also be fixed or synchronously move at high speed in various forms such as swinging when traveling along the welding direction. At this time, the swinging shape may include various shapes such as a circle, a broken line, an 8-shaped shape, an ∞-shaped shape, etc. The swinging frequency is generally 50-500HZ, and the swinging amplitude is between 0.2-1.5mm. In the welding process, a variety of single or mixed shielding gases may also be added, such as Ar gas, He gas, etc., or it may be carried out without shielding gas.

[0072] When the welding wire is used for feeding during the welding process, the wire feeding device can be replaced by a feeding device such as MAG (metal active gas), MIG (metal inert gas), or TIG (tungsten inert gas). The welding wire can be a solid wire or a flux-cored wire. The solder addition method can also be a composite of two different devices, such as two filler devices, which respectively feed different solders, one feeding a solder containing a certain component, and the other feeding a solder of another component, and the two solders are matched to achieve the final feeding into the molten pool so that the average aluminum content in the obtained preliminary weld does not exceed 1.8% by mass, preferably not higher than 1.5%; and the average micro-Vickers hardness of the obtained preliminary weld area is not less than 470HV, and the obtained structure is mainly lath martensite. When used as a higher strength match, such as a 2000Mpa grade material, the average micro-Vickers hardness of the obtained preliminary weld is not less than 570HV. In addition, the welding wire 4 can also be added by multiple steps or multiple parts; for example, the solder 4 is composed of two independent welding wires, and the average mass composition ratio of the final two solder combinations meets the content of the present invention. At the same time, the obtained preliminary weld is a weld with upper and lower excess heights, and the upper and lower excess heights h0 and h1 are not less than 5% of the average thickness of the two workpieces, such as Figure 6 As shown, B1 and B2 are the thicknesses of the two butted workpieces.

[0073] During the laser welding process, the laser beam acts on the welding wire and the base material at the same time to melt both of them. The melted welding wire forms a molten droplet that stably transitions to the welding pool. Generally, the laser welding power is 3-10KW, and the welding speed is not less than 3m / min. The spot area formed by the laser beam irradiating the surface of the workpiece assembly can be circular or other shapes. When it is circular, its diameter is not less than 0.3mm, and when it is other shapes, its equivalent circle diameter is not less than 0.3mm. The wire feeding speed of the welding wire during welding is generally 1-5m / min, and its ratio to the welding speed is between 0.3-1.5. The welding wire is iron-based and contains one or more austenitizing elements such as Ni, Mn, and C. The negative effects of the aluminum element melted into the weld are offset by delivering austenitizing elements during laser welding, eliminating the influence of ferrite.

[0074] The preliminary laser welded joint obtained above is subjected to quenching heat treatment, wherein the process includes heating and heat preservation, rapid cooling and slow cooling stages; Figure 7Shown is a schematic diagram of processing temperature changes. In this process, the preliminary welded joint is first kept warm for a time of t0 in an environment with a temperature of T0; wherein the temperature T0 satisfies: T0>930-400C-15Mn+50Si+5Cr; wherein C, Mn, Si, Cr are the mass percentage contents of the elements contained in the high-strength steel substrate, and T0 is generally 850-960℃; generally t0 is 150-500s, and satisfies t0≥B*150, B is the thickness of the maximum thickness of the two workpieces, in mm, and t0 is in seconds; at this stage, the weld zone and the base material zone are fully austenitized and transformed into austenite, and elements such as C, Mn, Al diffuse and tend to be evenly distributed; wherein the heating method can be heated by a gas medium, the workpiece as a whole is placed in an air furnace or a vacuum heat treatment furnace and other gas atmosphere heating furnaces, or heated by a liquid medium, the workpiece as a whole or the welded part is immersed in oil or salt in the heating temperature range, the oil is oil for conventional heat treatment oil bath, and the salt is salt for low temperature salt bath.

[0075] After the heating and heat preservation is completed, the weldment is quickly transferred to the next cooling device and rapidly cooled. The transfer process generally takes no more than 15 seconds. At this time, the workpiece temperature is T1, which exceeds 600°C. A rapid cooling process is performed, and the weldment is rapidly cooled from temperature T1 to T2 within t2. The cooling rate of the process exceeds the critical cooling rate of martensitic transformation, and the final temperature T2 satisfies: 150°C≤T2≤Ms-50°C; Ms is the critical temperature of the martensitic transformation of the steel workpiece substrate, and generally Ms does not exceed 400°C. Generally, the process can be completed in a solid mold or liquid medium with a certain temperature, for example, a hot stamping process is performed by maintaining a constant temperature solid mold, the mold is maintained at a certain temperature T, which is generally lower than T2, and then rapid stamping cooling is performed. The pressure applied in the process is generally not less than 3Mpa. Under rapid stamping cooling, the internal austenite of the weldment is transformed into a quenched martensite structure. The process t2 generally does not exceed 20s, preferably not more than 10s. Then, the quenching process can also be carried out in a liquid medium, such as a container filled with oil or salt, and the weld is quickly cooled in the liquid medium to cause a martensitic transformation. Generally, the temperature of the liquid is not less than 150°C. Both the base material and the weld area of ​​the weld undergo a martensitic transformation to form quenched martensite, and then slow cooling is performed to cause the quenched martensite to undergo self-tempering and transform into tempered martensite. The temperature of the weld drops from T2 to room temperature. Generally, the process takes a time t3 of not less than 10s. It is worth mentioning that when the aforementioned rapid cooling stage is completed in a pressure mold, the subsequent slow cooling stage can be completed by natural cooling in the air or by cooling in other media. When the aforementioned rapid cooling process is cooled in a liquid medium, the subsequent slow cooling can be completed by continuing to keep it in the liquid for a period of time, then taking it out and air cooling it in a natural environment, such as Figure 8 The liquid medium can be various media such as oil, salt, etc. that can be used for heating.

[0076] After the process is performed, the base metal area and the weld area of ​​the weld joint are transformed into tempered martensite, wherein: the weld joint includes a base metal area and a weld melting area; wherein the average micro-Vickers hardness of the base metal area and the melting area is HV BM 、HV FZ , and meet HV BM / HV FZ Between 0.8-1.2, preferably between 0.85-1.1, more preferably between 0.95-1.05; HV BM ≥470HV, preferably HV BM≥520HV; and the carbon content of the parent metal area is not less than 0.2% by mass, preferably not less than 0.25%; the average aluminum content of the weld area is not higher than 1.8% by mass, preferably not more than 1.5%. This structure can be used to manufacture various parts for locomotives, such as automobile A and B pillars, door ring structures. The tensile strength of the joint exceeds 1500Mpa, even more than 1700Mpa, the elongation exceeds 5%, and the tensile fracture failure occurs in the parent metal area, with excellent comprehensive performance.

[0077] Example 1

[0078] like Fig. 9 The figure shows a cross-sectional view of a final weld obtained by the method of the present invention, wherein the welded raw material is an aluminum silicon coating with a coating thickness of about 30 μm on both the upper and lower surfaces, the content of each element of which is shown in Table 1, and the thickness of which is 1.5 mm.

[0079] Table 1

[0080] C Mn Si Cr 930-400C-15Mn+50Si+5Cr Temperature T0(℃) Example 1 0.3 1.8 0.1 0.3 814.7 930 Example 2 0.3 1.0 0.2 0.3 797.5 930 Example 3 0.38 1.0 0.28 0.19 778 930 Example 4 0.33 0.53 0.47 0.02 788.4 930 Example 5 0.28 1.0 0.3 0.3 819.5 930

[0081] The Ni element added to the welding wire during the laser welding process accounts for about 7%. After welding, the initial weld is placed in a heating furnace with a heating temperature T0 of 930°C and a holding time of about 300s. It is then quenched in a salt bath at a temperature of 250°C for 30s and then quickly cooled and air-cooled to obtain the final weld joint. The final weld is an X-shaped weld as a whole, and the weld is mainly tempered lath martensite, such as Fig.10 As shown in Table 2, the average mass fraction of Al element is about 1.4%; the upper and lower surface residual heights are about 0.3 mm; the micro-Vickers hardness of the weld area and the base metal area is shown in Table 2;

[0082] Table 2

[0083]

[0084] Fig.11 The figure shows the mechanical properties test results of the laser welded joint after standard tensile specimen preparation. The results show that both specimens broke and failed in the parent material area, the tensile strength of the joint reached more than 1800Mpa, and the elongation exceeded 7%.

[0085] Example 2

[0086] like Fig.12Shown is a cross-sectional view of a final weld obtained using the method of the present invention. The original material to be welded is an aluminum-silicon coating with a thickness of about 30 μm on both the upper and lower surfaces, the content of each element of which is shown in Table 1, and the thickness is 2.0 mm. The Ni element of the welding wire added during the laser welding process accounts for about 7%. After welding, the initial weld is placed in a heating furnace with a heating temperature T0 of 930°C and a holding time of about 360s. It is then quenched in a salt bath at a temperature of 230°C at T2 for 30s and then rapidly cooled and taken out for air cooling to obtain the final weld joint. The final weld is X-shaped as a whole, and the weld is mainly tempered lath martensite, such as Fig.13 As shown in Table 2, the average mass fraction of Al element is about 1.3%; the upper and lower surface residual height is about 0.2mm; the micro-Vickers hardness of the weld area and the base metal area is shown in Table 2;

[0087] Fig.14 The figure shows the mechanical properties test results of the laser welded joints after standard tensile specimen preparation. The results show that all three specimens failed in the parent material area, the tensile strength of the joints reached more than 1900Mpa, and the elongation exceeded 5%, meeting the use requirements.

[0088] Example 3

[0089] like Fig.15 Shown is a cross-sectional view of a final weld obtained using the method of the present invention. The original material to be welded is an aluminum-silicon coating with a thickness of about 30 μm on both the upper and lower surfaces, the content of each element of which is shown in Table 1, and the thickness is 1.8 mm. The Ni element of the welding wire added during the laser welding process accounts for about 7%. After welding, the initial weld is placed in a heating furnace with a heating temperature T0 of 930°C and a holding time of about 360s. It is then quenched in a salt bath at a temperature of 210°C at T2 for 30s and then rapidly cooled and taken out for air cooling to obtain the final weld joint. The final weld is X-shaped as a whole, and the weld is mainly tempered lath martensite, such as Fig.16 As shown in Table 2, the average mass fraction of Al element is about 1.3%; the upper and lower surface residual height is about 0.2mm; the micro-Vickers hardness of the weld area and the base metal area is shown in Table 2;

[0090] Fig.17 The figure shows the mechanical properties test results of the laser welded joints after standard tensile specimen preparation. The results show that all three specimens failed in the parent material area, the tensile strength of the joints reached more than 1900Mpa, and the elongation exceeded 7%, meeting the use requirements.

[0091] Example 4

[0092] like Fig.18Shown is a cross-sectional view of a final weld obtained using the method of the present invention. The original material to be welded is an aluminum-silicon coating with a thickness of about 30 μm on both the upper and lower surfaces, the content of each element of which is shown in Table 1, and the thickness is 1.2 mm. The Ni element of the welding wire added during the laser welding process accounts for about 7%. After welding, the initial weld is placed in a heating furnace with a heating temperature T0 of 930°C and a holding time of about 300s. It is then quenched in a salt bath at a temperature of 200°C at T2 for 30s, rapidly cooled, and then taken out for air cooling to obtain the final weld joint. The final weld is X-shaped as a whole, and the weld is mainly tempered lath martensite, such as Fig.19 As shown in Table 2, the average mass fraction of Al element is about 1.2%; the upper and lower surface residual heights are about 0.3 mm; the micro-Vickers hardness of the weld area and the base metal area is shown in Table 2;

[0093] Fig. 20 The figure shows the mechanical properties test results of the laser welded joints after standard tensile specimen preparation. The results show that all three specimens failed in the parent material area, the tensile strength of the joints reached more than 1900Mpa, and the elongation exceeded 7%, meeting the use requirements.

[0094] Example 5

[0095] like Fig.21 Shown is a cross-sectional view of a final weld obtained using the method of the present invention. The original material to be welded is an aluminum-silicon coating with a thickness of about 9 μm on both the upper and lower surfaces, the content of each element of which is shown in Table 1, and the thickness is 1.8 mm. The Ni element of the welding wire added during the laser welding process accounts for about 7%. After welding, the initial weld is placed in a heating furnace with a heating temperature T0 of 930°C and a holding time of about 300s. It is then quenched in a salt bath at a temperature of 200°C at T2 for 30s, rapidly cooled, and then taken out for air cooling to obtain the final weld joint. The final weld is X-shaped as a whole, and the weld is mainly tempered lath martensite, such as Fig. 22 As shown in Table 2, the average mass fraction of Al element is about 1.0%; the upper and lower surface residual heights are about 0.3 mm; the micro-Vickers hardness of the weld area and the base metal area is shown in Table 2;

[0096] Fig.23 The figure shows the mechanical properties test results of the laser welded joints after standard tensile specimen preparation. The results show that all three specimens failed in the parent material area, the tensile strength of the joints reached more than 1800Mpa, and the elongation exceeded 8%, meeting the use requirements.

[0097] Comparative Example 1

[0098] like Fig.24The figure shows the mechanical properties and fracture of the welded joint obtained by laser welding using the same raw materials as in Example 1, keeping the weld at 930°C for 5 minutes, and quickly cooling it to room temperature in water. It can be seen that they all broke and failed at the weld position, with an average fracture strength of only 1394 MPa and an elongation of 2.66, which does not meet the use requirements.

[0099] Comparative Example 2

[0100] like Fig.25 The figure shows the mechanical properties and fracture of the welded joint obtained by laser welding using the same raw materials as in Example 2, keeping the temperature at 930°C for 5 minutes after welding, and transferring the welded joint to a flat mold with a coolant flowing therethrough for rapid cooling to about 100°C. It can be seen that the welded joints all broke and failed at the weld position, with an average fracture strength of only 1335 MPa and an elongation of 3.1, which do not meet the use requirements.

Claims

1. A hot-formed steel laser welding joint, characterized in that: The weld joint comprises a base metal zone and a weld melting zone; wherein the average micro-Vickers hardness of the base metal zone and the melting zone is HV BM 、HV FZ , and satisfies HV BM / HV FZ Between 0.8-1.2, HV BM ≥470HV , The microstructures of the parent material area and the weld area are composed of tempered martensite, and the carbon content of the parent material area is not less than 0.2% by mass, and the average aluminum content of the weld area is not higher than 1.8% by mass.

2. The hot-formed steel laser welding joint according to claim 1, characterized in that: The HV BM / HV FZ Between 0.85-1.

1.

3. The hot-formed steel laser welding joint according to claim 1 or 2, characterized in that: The average aluminum content of the weld zone is not higher than 1.5% by mass.

4. The hot-formed steel laser welding joint according to claim 1, characterized in that: HV BM ≥520HV, and the carbon content in the parent metal area is not less than 0.25% by mass.

5. The hot-formed steel laser welding joint according to claim 4, characterized in that: HV BM ≥550HV, and the carbon content in the parent metal area is not less than 0.30% by mass.

6. A method for making a hot-formed steel laser welding joint, characterized in that: The method comprises the following steps: a) providing a pair of high-strength steel workpieces butted together to form an assembly; b) performing laser welding on the assembly to form a preliminary weld joint, wherein the initial weld molten zone forms quenched martensite; c) performing a quenching treatment on the preliminary welded joint, including a heating and heat preservation stage and a cooling stage: Heating and holding stage: the weld joint is kept in an environment of temperature T0 for a holding time t0, wherein T0 is 820-980°C, t0 is 150-500s, t0≥B*150, B is the thickness of the assembly, in mm, so that the quenched martensite in the initial weld melting zone is transformed into austenite, and the base material zone forms austenite; Cooling stage: divided into rapid cooling stage and slow cooling stage. The rapid cooling stage refers to the rapid transfer and rapid cooling of the joint after heating and heat preservation, wherein the transfer time is t1, t1≤15s, the initial temperature of rapid cooling is T1, T1≥600°, and the cooling time from T1 to T2 is not less than 30° / s, so that the parent material area and the weld melting area are transformed into quenched martensite, wherein 2≤t2≤20s; 150℃≤T2≤Ms-50℃, Ms is the critical temperature of martensitic phase transformation of high-strength steel substrate; Slow cooling stage: The base metal area and the weld melting area are cooled to room temperature, and self-tempering occurs to transform the quenched martensite into tempered martensite.

7. The method for manufacturing a hot-formed steel laser welding joint according to claim 6, characterized in that: At least one surface of the steel workpiece has an aluminum coating.

8. The method for manufacturing a hot-formed steel laser welding joint according to claim 6, characterized in that: T0> 930-400C-15Mn+50Si+5Cr; wherein C, Mn, Si and Cr are the mass percentage contents of the elements contained in the high-strength steel substrate.

9. The method for manufacturing a hot-formed steel laser welding joint according to any one of claims 6 to 8, characterized in that: The carbon content of the steel substrate is not less than 0.2% by mass.

10. The method for manufacturing a hot-formed steel laser welding joint according to claim 9, characterized in that: The carbon content of the steel substrate is not less than 0.25% by mass.

11. The method for manufacturing a hot-formed steel laser welding joint according to any one of claims 6 to 8, characterized in that: The laser welding process adopts a laser wire-filling welding method, and the austenitizing elements Ni, Mn and C are synchronously transported into the weld molten pool during the welding process.

12. The method for manufacturing a hot-formed steel laser welding joint according to claim 6, characterized in that: The martensitic transformation critical temperature Ms of the steel substrate is no more than 400°C.

13. The method for manufacturing a hot-formed steel laser welding joint according to claim 6, characterized in that: The tensile strength of the steel substrate after final quenching is not less than 1500 MPa.

14. Use of a welded joint according to any one of claims 1 to 5 or a component obtained by any one of the methods of claims 6 to 14 in a structural component or a safety component of a mechanized land vehicle.

Citation Information

Patent Citations

  • A heat treatment method to improve the plasticity of laser-welded joints of high-strength, high-ductility manganese steel

    CN108356417B

  • A spot welded joint of a high-strength steel plate and its manufacturing method

    CN112222667B

  • Manufacturing method for hydrogen induced cracking resistant laser welding joint of plating-free hot forming steel

    CN116748681A

  • Method for reducing cracking sensitivity of Mn-B series hot forming steel part

    CN117070845A

  • 2.0 GPa grade Cu-containing hot forming steel plate and preparation method thereof

    CN117737372A

Cited By

  • Method for resisting hydrogen embrittlement of welded joint of aluminum-silicon coating hot-formed steel tailor-welded blank and application of method

    CN121718693A